Sand, water, silence--the embodiment of spirit : explorations in matter and psyche - Markell, Mary Jane, 1936- (Jessica Kingsley, 2002)
Therapists often encounter people who have suffered severe emotional damage resulting in feelings of psychological fragmentation. Sandplay therapy, which combines the physical actions of play with observation and understanding through the use of symbolism, can be a useful method of treating this kind of damage. This book focuses on the theoretical aspects of sandplay therapy, presenting Dora M. Kalff's ideas and drawing out the significance of Kalffian sandplay for therapists. Building on Kalffian ideas of the integration of Eastern and Western thought in relation to healing through sandplay.